Epigenetics and Neuroinflammation Associated With Neurodevelopmental Disorders: A Microglial Perspective - Komada, Munekazu; Nishimura, Yuhei (Frontiers in Cell and Developmental Biology, 2022)
Neuroinflammation is a cause of neurodevelopmental disorders such as autism spectrum disorders and fetal alcohol syndrome. Converging lines of evidence from basic and clinical sciences suggest that dysregulation of the epigenetic landscape, including histone modification, DNA methylation, and microRNA expression, is associated with neuroinflammation. Both genetic and environmental factors can affect the interaction between epigenetics and neuroinflammation, which may cause neurodevelopmental disorders. In this minireview, we focus on epigenetic dysregulation in microglia, which regulate neuroinflammation, and compare studies using mammals and zebrafish.